FORMULATION STRATEGY, STABILITY ISSUES, SAFETY AND EFFICACY EVALUATIONS OF ACACIA CATECHU WHITENING CREAM - Anurukvorakun, Oraphan; Lahpun, Narongrit; Boonruang, Rachadaporn (International Journal of Applied Pharmaceutics, 2019)
Objective: To investigate among formulation strategy, stability issues, safety and efficacy (tyrosinase inhibitory activity and sun protection) of a novel whitening cream containing Acacia catechu heartwood extract. Methods: The tyrosinase inhibitory activity of the A. catechu extract was investigated using L-DOPA as a substrate. A combination of silicone and three photo-protective filters; natural UV filter (A. catechu extract), chemical and physical filters, was formulated and evaluated. The Sun Protection Factor (SPF), stability, skin allergy or irritation, and the satisfaction of the developed whitening creams, were investigated. Results: The A. catechu extract showed the strong tyrosinase inhibitory activity with the percentage of inhibition of 61.58% at the concentration of 120 mg/ml compared to a positive control of kojic acid (98.73 % inhibition) at the same concentration of 120 mg/ml. impressively, the highest SPF of A. catechu whitening cream with physical and chemical UV filters was 30. While, the highest SPF of the A. catechu whitening cream without those filters, was 24. No changes in color, liquefaction and phase separation were observed for the developed whitening cream when stored in the refrigerator. Among the twenty volunteers, eighteen volunteers had no skin irritation, while one of them had redness (Transient) and then another one had erythema or very slight irritation to the developed whitening creams. Besides, there was no statistically significant difference for the satisfaction between A. catechu whitening creams and commercial whitening creams (p>0.05). Conclusion: Obviously, A. catechu whitening creams had very high efficacy, stability, and safety for being a commercial product in a near future.